1999
DOI: 10.1034/j.1399-0004.1999.550106.x
|View full text |Cite
|
Sign up to set email alerts
|

Nevoid basal cell carcinoma syndrome. Clinical findings in 37 Italian affected individuals

Abstract: Nevoid basal cell carcinoma syndrome (NBCCS) is a hereditary condition transmitted as an autosomal dominant trait with complete penetrance and variable expressivity. The syndrome is characterised by numerous basal cell carcinomas (BCCs), odontogenic keratocysts of the jaws, palmar and/or plantar pits, skeletal abnormalities and intracranial calcifications. In this paper, the clinical features of 37 Italian patients are reviewed. Jaw cysts and calcification of falx cerebri were the most frequently observed anom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
168
3
9

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(188 citation statements)
references
References 18 publications
8
168
3
9
Order By: Relevance
“…3,[29][30][31][32][33] Comparison of the frequencies of major phenotypes in NBCCS, such as BCCs, KCOTs, palmar or plantar pits and calcification of the falx cerebri are listed in Table 4. Obvious differences were found in the onset of BCCs.…”
Section: Discussionmentioning
confidence: 99%
“…3,[29][30][31][32][33] Comparison of the frequencies of major phenotypes in NBCCS, such as BCCs, KCOTs, palmar or plantar pits and calcification of the falx cerebri are listed in Table 4. Obvious differences were found in the onset of BCCs.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Previous studies on the skeletal malformations in NBCCS include the following: Dunnick et al 4 reported the incidence of radiological features in 27 individuals with NBCCS evaluated at the National Institutes of Health before 1978. Four population-based studies, one each from the UK, 5 Australia, 6,7 USA, 8 and Italy 9 have reported the frequency of the clinical features in NBCCS patients. Kimonis et al 8 reported the important clinical features in 105 individuals with NBCCS in a large US cross-sectional study conducted at the National Institute of Health.…”
mentioning
confidence: 99%
“…Odontogenic keratocysts are often the first sign of NBCCS and arise earlier in patients with the syndrome than in patients unaffected by the syndrome 9 . The most frequent skin lesions for NBCCS are BCCs.…”
Section: Discussionmentioning
confidence: 99%